Faculty status for Nigerian university librarians: the Ibadan university case (1980)
The fight for faculty status by university librarians has been on for more than a century and is still being debated the world over today. The writer outlines the meaning of faculty status and how it affects university librarians in developing country- Nigeria. Suggested solutions to this problem are made including the recognisation of the Ibadan university library step-up to reflect a faculty with corresponding faculty titles and ranks.